Seroprevalence of Toxoplasma gondii, Rubella and Cytomegalovirus Among Pregnant Refugees and Turkish Women: A Retrospective Comparative Study - Lütfiye Nilsun Altunal; Ayşe Banu Esen; Gül Karagöz; Kadriye Kart Yaşar (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]To evaluate the prevalence of Toxoplasma gondii, rubella and cytomegalovirus (CMV) among the pregnant Turkish women as well as Syrian refugees in Istanbul.[¤]METHODS[|]Among pregnant women who are admitted to \\\"xxxx\\\" Maternity and Children Hospital in İstanbul between January 2014 and January 2015, antibodies against Toxoplasma gondii, rubella and CMV were measured using the micro-elisa method. The test results were evaluated retrospectively.[¤]RESULTS[|]Out of total 1066 pregnant women screened in this study, 963 (90.3%) were Turkish, and 103 (9.7%) were Syrian refugees. IgM positivity rates of T. gondii rubella and CMV were determined as 0,2%, 0%, 0,2% in Turkish women and 0,1%, 0%, 0% in Syrian refugees, IgG positivity rates were determined as 26,3%, 93,8%, 99,5% in Turkish women and 58,3%, 87,4%, 100% in Syrian refugees. The seroprevalence of T. gondii was lower and the rubella seroprevalence was higher among pregnant Turkish women and among pregnant Syrian refugees and statistically significant ( p< 0.05).[¤]DISCUSSION AND CONCLUSION[|]Since immunity against T. gondii in pregnant Turkish women is lower than in Syrian refugees, who are in reproductive age group, should get routine screenings. Immunization against rubella should be considered for Syrian refugees who are in reproductive age group. [¤]